AB0657 Discontinuation of Anti-TNF Therapy in Patients with Axial Spondyloarthritis in Clinical Practice: Prevalence and Causes. (15th July 2016) - Moral, E.; Plasencia, C.; Navarro-Compán, V.; Pascual Salcedo, D.; Jurado, T.; Tornero, C.; Pierens, A.; Paredes, M.B.; Bogas, P.; Monjo, I.; Martin Mola, E.; Balsa, A.
Abstract : Background: The majority of patients with axial spondyloarthritis (SpA) response to anti-TNF therapy. However, discontinuation of this therapy due to different reasons is still a relevant problem. Currently, there is not enough data to know exactly which is the prevalence and causes of interruption of anti-TNF therapies in clinical practice. Objectives: First, to evaluate the frequency and causes of discontinuating adalimumab or infliximab as the first anti-TNF in patients with axial SpA in clinical practice. Second, to investigate the influence of anti-drug antibodies (ADA) on these causes. Methods: A total of 326 patients with axial SpA who had received adalimumab (34%) or infliximab (66%) as a first anti-TNF therapy were included in this retrospective, observational study performed in a tertiary hospital. Disease activity (BASDAI, ASDAS, CRP and ESR) was measured before starting anti-TNF therapy, after 6 months and when interrupting the therapy to assess properly whether the reason for discontinuation was primary or secondary failure. Serum drug levels and/or ADA were measured at 6 months visit and at the end of anti-TNF treatment. Results: A total of 99 (30.4%) patients discontinued treatment. Mean (SD) under anti-TNF therapy until discontinuation was 2.5 (2.9) years. Characteristics of these patients when initiating anti-TNF therapy are shown in Table 1 . The reason to interrupt treatment was: primary failure in 22.2%, secondary failure in 36.4%, side effects 32.3%), and other reasons in 9.1%. Serum drug levels and ADA were available in 83 patients. In most patients with ADA positive (14/17), the reason for discontinuation was secondary failure. Out of those patients who discontinued due to secondary failure, 38.9% had ADA positive. Conclusions: In our cohort of patients with axial SpA treated with adalimumab/infliximab, 30% of patients discontinued anti-TNF therapy. The main reason to discontinue treatment was secondary failure, which was related to the presence of ADA in almost 40% of patients. Disclosure of Interest: E. Moral Grant/research support from: Funded by an unrestricted medical grant from Pfizer, C. Plasencia: None declared, V. Navarro-Compán: None declared, D. Pascual Salcedo: None declared, T. Jurado: None declared, C. Tornero: None declared, A. Pierens: None declared, M. B. Paredes: None declared, P. Bogas: None declared, I. Monjo: None declared, E. Martin Mola: None declared, A. Balsa: None declared